Employment Counsellors' and Youths' Views of the Transition to Work: Preparing to Develop a Work Skills Simulation - Cairns, Kathleen V.; Woodward, J. Brian; Hashizume, Laurie G. (Canadian Journal of Counselling and Psychotherapy, 1992)
The transition to work life is often difficult for adolescents and youth. This paper reviews the transition literature and discusses the results of interviews with youth counsellors and with youth themselves regarding their views of the transition process, barriers or obstacles to successful transitions, characteristics of successful transitions, and the meaning ofwork. Youth and counsellors consistently identified employment skills, employer characteristics, and social support as important factors in the transition. However, youth counsellors also noted the influence of employment attitudes and expectations while youth stressed the impact of job search experiences and their need for personal fulfillment through work. The purpose of this paper is to provide a perspective on the current sense of professional identity amongst counsellors and counselling psychologists in Canada, with the hope of encouraging more attention to this issue amongst counsellors, counselling psychologists, and counsellor educators. Findings from a pilot survey on professional identity suggest that the three groups agree on the definition of counselling psychology, but there are considerable discrepancies between the perceptions and practices of all three groups. As well, there is little agreement on how counselling psychology is similar to or different from other helping professions. Conclusions and implications of these findings for the development of a more clear professional identity are discussed.